2019
DOI: 10.31680/gaunjss.621767
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship Between Self-Talk and Mental Toughness Levels of the Students in the Faculty of Sports Sciences

Abstract: Bu çalışmanın temel amacı; spor bilimleri fakültesindeki sporcu öğrencilerin kendinle konuşma ve zihinsel dayanıklılık düzeyleri arasındaki ilişkinin incelemesidir. Çalışmaya Akdeniz ve Gazi Üniversitelerinin Spor Bilimleri Fakültelerinde öğrenim görmekte olan rastgele yöntemle seçilmiş 198 sporcu öğrenci katılmıştır. Katılımcıların 86'sı kadın (%43,4), 112'si erkektir (%56,6). Araştırma kapsamında veriler, araştırmacılar tarafından hazırlanan Kişisel Bilgi Formu, Sporda Zihinsel Dayanıklılık Envanteri (SZDE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
2
0
4
Order By: Relevance
“…When similar studies are examined, as a result of the study conducted by Gülşen, Şahan, Yıldız, and Yılmaz (2019) on the students of the faculty of sports sciences, it is observed that there is a low positive relationship between mental toughness and motivational self-talk, a moderate positive relationship between mental toughness and cognitive self-talk, and a low positive relationship between mental toughness and self-talk total score. Coulter, Mallett, and Gucciardi (2010) have reported in their study on football players that they talk to themselves when they require mental toughness.…”
Section: Discussionmentioning
confidence: 99%
“…When similar studies are examined, as a result of the study conducted by Gülşen, Şahan, Yıldız, and Yılmaz (2019) on the students of the faculty of sports sciences, it is observed that there is a low positive relationship between mental toughness and motivational self-talk, a moderate positive relationship between mental toughness and cognitive self-talk, and a low positive relationship between mental toughness and self-talk total score. Coulter, Mallett, and Gucciardi (2010) have reported in their study on football players that they talk to themselves when they require mental toughness.…”
Section: Discussionmentioning
confidence: 99%
“…Bu sürecin verimli ilerlemesi, kişi de özgüven duygusunun oluşmasına, kişiler arası iletişime ve geleceğe dair yapacakları planlamalara olumlu anlamda katkı sağlayabilmektedir. Nitekim spor ortamında bilişsel faktörlerin önemi yapılan araştırmalar ile ortaya konulmuştur (Yarayan ve Ayan, 2018;Yarayan, Yıldız ve Gülşen, 2018;Gülşen, Yıldız, Yılmaz ve Şahan, 2019;Tutal ve Efe, 2019;Tutal ve Efe, 2020;Arı ve diğerleri, 2020;Çiftçi, Tolukan ve Yılmaz, 2021). İsabetli karar verme sürecinin sonucu olarak kişinin yaşantısının olumlu anlamda etkilenmesi beklendik bir durumdur (Dereli ve Acat, 2011).…”
Section: Introductionunclassified
“…Nitekim sporcu başarılı olmak için birçok fiziksel engelin yanında kaygı ve endişe gibi çokça psikolojik engeli de aşmak zorundadır (Biçer, 2008). Bu kapsamda sporcuların psikolojik yapılarının ele alındığı araştırmalarda zihinsel dayanıklılık (Gülhan ve Şahin, 2021;Gülşen, Yıldız, Yılmaz ve Şahan, 2019;Yarayan, Yıldız ve Gülşen, 2018), zihinsel antrenman (Cankurtaran, 2020;Çiftçi, Tolukan ve Yılmaz, 2020;Yarayan ve İlhan, 2018) ve atletik zihinsel enerji (Gülşen, Eryücel, Turna, Yıldız ve Eryücel, 2021;Chiou ve diğerleri, 2020;Yıldız, Yarayan, Yılmaz ve Kuan, 2020;Lu ve diğerleri, 2018) gibi güncel psikolojik becerilerin yanında duygusal zekâ ve kişilik de sürekli olarak ilgi gösterilen kavramlar olarak karşımıza çıkmaktadır. Çünkü duygusal zekâ ve kişilik özellikleri sportif rekabet içerisinde önemli birer belirleyici olabilmektedir.…”
Section: Introductionunclassified